Pengembangan Modul Elektronik Dengan Feedback Berbasis Android Materi Suhu Dan Kalor Untuk Siswa SMA/MA - Amaliyah Tazkiyah; Sulur Sulur; Sahal Fawaiz (Jurnal Pendidikan Fisika dan Teknologi (JPFT), 2020)
The integration of ICT in the learning process has a positive effect on students' concepts understanding and learning interests. Android is a learning media tool that can store lots of interesting learning materials, such as electronic modules. This study was conducted to determine the feasibility of an Android-based electronic module with temperature and heat material feedback for high school / MA students. This research method is used in the ADDIE model (analysis, design, development, implementation, and evaluation). The electronic module was tested for validation by the validator with an average value of 3.49 and the module readability test with respondents of 85 students who obtained an average value of 79.3%. Based on the data obtained, it can be conclude that the electronic module has decent criteria.